Establishing quality indicators to comprehensively assess quality assurance and patient safety in radiotherapy and their relationship with an institution's background. (February 2023) - Mizuno, Norifumi; Okamoto, Hiroyuki; Minemura, Toshiyuki; Kawamura, Shinji; Tohyama, Naoki; Kurooka, Masahiko; Kawamorita, Ryu; Nakamura, Masaru; Ito, Yoshinori; Shioyama, Yoshiyuki; Aoyama, Hidefumi; Igaki, Hiroshi
Highlights: Quality indicators (QIs) were established to assess quality assurance and safety. An initial survey was conducted on QIs and the institutional background. The median QI achievement rate was 60.8%. Variation was observed depending on the facility size and the treatment type. The results will contribute to policy recommendations for improving patient safety. Abstract: Background and purpose: Quality indicators (QIs) for radiotherapy have been proposed by several groups, but no study has been conducted to correlate the implementation of indicators specific to patient safety over the course of the clinical process with an institution's background. An initial large-scale survey was conducted to understand the implementation status of QIs established for quality assurance and patient safety in radiotherapy and the relationship between implementation status and an institutions' background. Materials and method: Overall, 68 QIs that were established by this research team after a pilot survey were used to assess structures and processes for quality assurance and patient safety. Data on the implementation of QIs and the institutions' backgrounds were obtained from designated cancer care hospitals in Japan. Results: Overall, 284 institutions (72 %) responded and had a median QI achievement rate of 60.8 %. QIs with low implementation rates, such as the implementation of an error reporting system and establishment of a quality assurance department, were identified. The QI achievement rate and scale of the institution were positively correlated, and the achievement rate of all QIs was significantly higher ( p  < 0.001) in institutions capable of advanced treatments, such as intensity-modulated radiotherapy, and those with a quality assurance department. Conclusion: A large-scale survey on QIs revealed their implementation and relationship with a facility's background. QIs that require improvement were identified, and that these QIs might be effective in providing advanced medical care to many patients.